Saints in the National Memory Cultures of the 20th Century: The Cases of Saint Casimir and Saint Josaphat - Streikus, Arūnas (Lietuvos istorijos studijos, 2025)
The article examines the 20th-century histories of the veneration of Saint Casimir and Saint Josaphat Kuntsevych, seeking to answer the following questions: Does the development of these cases correlate with tendencies to instrumentalize national patrons in other contexts, or does it challenge them? Where do the 20th-century trajectories of the veneration of St. Casimir and St. Josaphat overlap, and where do they diverge? And why were neither of them included among the top-tier people of the pantheons of national heroes in the 20th century? The review analysis essentially confirms the insights of other researchers regarding the adaptability of such sites of memory across different contexts and their particular relevance to diasporic communities. The analysis also reveals the obstacles which prevented St. Josaphat from transcending the boundaries of religious veneration and becoming a national hero. Although the research found that St. Casimir did surpass these boundaries, he did not attain the status of a national patron due to competition with other sites of memory.
Keywords: memory culture; saints; national patrons; the Holy See